Do Higher Fees Imply Better Performance? An Insight to Fee-performance Relationship in the US Mutual Fund Industry. - FAN, YI (2008)
Recent studies propose that equity mutual fund managers generally do not have ability to generate abnormal returns to outperform the market, and their performance bear negative relationship with the expenses charged when investors invest in mutual funds. This study employs a data set including monthly returns from sixty equity mutual funds existing throughout the examined period from January 1998 to December 2007. These data are used to examine performance of actively managed mutual funds and the extent of the relationship between fund performance and incurred expenses. With subjection to survivorship bias, it is found that a few mutual funds but not aggregately outperformed the benchmark portfolio by providing higher risk-adjusted performance. Moreover, there was no relationship detected between fund performance and expense incurred.